Perkembangan Irigasi Pintar Pada Melon (Cucumis melo L) Hidroponik (Studi Literatur) - Qudrat Aini; Wahono; Agus Zainuddin; Fatimah Nursandi; Padhina Pangestika (Jurnal Galung Tropika, 2025)
Melon consumption has increased yearly due to the number of consumers. It requires rising production and land. The limited land area encourages the implementation of hydroponics with an irrigation system. This article aims to summarize various results of recent studies regarding the development and use of smart irrigation systems based on the Internet of Things and fuzzy logic in hydroponic melon cultivation using the Nutrient Film Technique method and drip irrigation. Water requirements greatly influence melon plants from vegetative growth to fruit ripening. The provision of water is carried out using the Nutrient Film Technique (NFT) irrigation technique, and drip irrigation is more optimal, requiring smart irrigation system technology. This system focuses on water supply according to plant needs, phenological phases, and environmental conditions. Based on the literature, two types of technology have been summarized: IoT-based irrigation can save water supply by up to 90% compared to the fuzzy logic method, which is around 29%. We hoped that a smart irrigation system for melons would increase the productivity of melon plants, especially hydroponic cultivation.